Local perspectives on tenure rights and conflict in FMU Rinjani Barat, West Nusa Tenggara Province - Cecep Handoko; Yumantoko (Foresty Faculty of Hasanuddin University, 2015)
Local perspectives on tenurial rights and conflict needs to be known in overcoming forest tenurial conflict thoroughly. Aiming at knowing this local perspective, study was conducted in FMU Rinjani Barat in 2013 at the villages of Senaru, Santong and Rempek, North Lombok District. Research activities included literatures review, and interview. Data were analyzed using CDA and multiple linier regression. Results indicated that there is need for rearrangement of forest rule and the propriety of the rule, improving forest management, and accommodation to various interests on forest land as well as resources. In high forest destruction condition, forest tenurial conflict resolution should be done in the context of sustainable management which was accompanied by an increase in communication, cooperation, alignment, and mentoring to community. Related to these efforts, law enforcement is needed for improving sustainability of management, and avoiding irregularities in implementation of forest management.